Boxing In The Field Of Pedagogy (Eurasian Journal of Learning and Academic Teaching, 2023)
Boxing in the field of pedagogy refers to the use of boxing techniques and principles in educational settings. It involves incorporating elements of boxing, such as discipline, focus, and physical activity, into teaching and learning processes. The concept of boxing in pedagogy focuses on the holistic development of individuals, combining cognitive, emotional, and physical aspects. It emphasizes the value of discipline, self-control, and perseverance, which are essential qualities in both boxing and education.